Oral Cysteamine bitartrate and N-acetylcysteine combination for patients with infantile neuronal ceroid lipofuscinosis:a pilot study - Levin, Sondra W. (2014)
BACKGROUND: Infantile neuronal ceroid lipofuscinosis (INCL) is a devastating neurodegenerative lysosomal storage disease caused by mutations in the CLN1 gene encoding palmitoyl-protein thioesterase-1 (PPT1). PPT1-deficiency causes lysosomal ceroid accumulation leading to INCL pathogenesis. Previously, we reported that phosphocysteamine and N-acetylcysteine mediated ceroid depletion in cultured cells from INCL patients. We conducted a pilot study to determine whether a combination of cysteamine bitartrate and N-acetylcysteine is beneficial for these patients. METHODS: Patients (6-month to 3-years old) with any combination of 2 of the 7 most lethal PPT1 mutations were admitted. All patients were recruited from physician referrals and the PPT1 mutations were analyzed prior to admission. Patients were evaluated by electroretinography(ERG), brain MRI and MRS, electroencephalography (EEG), and electron microscopic analyses of leukocytes for granular osmiophilic deposits (GRODs). Patients received oral cysteamine bitartrate (60mg/kg/day) and N-acetylcysteine (60mg/kg/day) and were evaluated every 6 to 12 months until they showed isoelectric EEG attesting to a vegetative state or were too sick to travel. Outcomes were compared with the reported INCL natural history. In two cases, the disease progression was compared with that of a sibling who was above the age limit for inclusion into the protocol. FINDINGS: Between March, 2001, and June, 2011, we recruited 10 children with INCL but one was lost to follow-up after the first visit. Thus, a total of 9 patients (5 females and 4 males) were studied. At the first follow-up visit, peripheral leukocytes in all 9 patients showed virtually complete depletion of GRODs and 7 of 9 patients manifested less irritability and/or improved alertness based upon parental and physician observations. Evaluation by Denver scale showed acquisition of no new developmental skills and retinal function assessed by ERG progressively declined. Most notably, average time to isoelectric EEG (indicating vegetative state) was significantly longer in our patients compared to that previously reported. MRI studies demonstrated signal abnormalities similar to previous reports. Brain volume and NAA declined steadily, but no published quantitative MRI or MRS studies of INCL patients are available for comparison on these measures. There were no adverse events related to therapy other than a mild gastrointestinal discomfort in 2 of 9 patients, which was eliminated when the liquid preparation of cysteamine bitatrate was replaced with capsules. INTERPRETATION: The objectively demonstrated benefits in our study are the depletion of GRODs and delay of isoelectric EEG in all patients; in addition, several subjective benefits were suggested, all of which warrant further study. Nevertheless, this report systematically and quantitatively documents the natural history of 9 INCL patients with the most lethal CLN1/PPT1 mutations and thereby provides a benchmark for evaluating future experimental therapies. FUNDING: This study was supported in part by a Bench-to-Bedside Award from the Clinical Center of the NIH and by the Intramural Program of the Eunice Kennedy Shriver National Institutes of Child Health and Human Development, NIH.